Exploring the Impact of Gamification on English Language Learning for Students in Asia Countries: A systematic review - Supasa, Aprilia Yunda; Ramadhani, Meutya Rizki; Ningrum, Fatma Setya; Hamuddin, Budianto (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
This study explores the effectiveness of gamification in English language learning in Asian countries, aiming to identify best practices and challenges in its integration. Although gamification has been widely acknowledged for enhancing student engagement and motivation, its impact on improving actual language proficiency remains uncertain, especially in the diverse educational contexts of Asia. Through a systematic review of literature published from 2019 to 2024, this research addresses gaps in existing studies, particularly those focusing on gamification within Asian educational systems. The review adheres to PRISMA guidelines, and data were gathered using the Publish or Perish tool, which identified 1,053 studies based on keywords such as "gamification," "impact," "English learning," and "Asia." Inclusion and exclusion criteria were rigorously applied to ensure the relevance of selected studies. The findings indicate that while gamification has the potential to increase motivation and engagement, several contextual factors—such as technological access, teacher preparedness, and cultural perceptions of game-based learning—are critical to its success. This study provides evidence-based recommendations for overcoming these challenges and offers practical strategies for educators and policymakers to design more effective gamified learning interventions that can enhance English language acquisition in Asia.